An open‐label evaluator‐blinded clinical study of minocycline neuroprotection in ischemic stroke: gender‐dependent effect. (23rd August 2014) - Amiri‐Nikpour, Mohammad Reza; Nazarbaghi, Surena; Hamdi‐Holasou, Milad; Rezaei, Yousef
Abstract : Objectives: Minocycline as an antibiotic has been found to have neuroprotective effect on neurodegenerative diseases. This study was aimed at determining the efficacy of minocycline adjunct to aspirin in improving neurological outcomes of ischemic stroke during 3‐month follow‐up. Methods and materials: In an open‐label evaluator‐blinded trial, 60 patients with ischemic stroke were allocated into two groups to receive either 200 mg of oral minocycline daily for 5 days during 6–24 h following onset of signs and symptoms, or not receiving any, as control; all patients also received 100 mg of aspirin daily. Clinical assessment at baseline and on days 30, 60, and 90 was performed using National Institutes of Health Stroke Scale (NIHSS) score. Results: Fifty‐three patients (88.3%) completed the study. Females in the treatment and control groups were 53.8% and 51.9%, respectively ( P  =   0.884). Among all patients, NIHSS score was significantly lower in the minocycline‐treated compared with control on day 90 (minocycline median 4, interquartile range 4–7, control median 7, interquartile range 5–8, P  =   0.031). Among males, NIHSS was lower in minocycline‐treated compared with controls on days 30, 60, and 90 ( P  <   0.05); however, females showed no significant differences at the same times compared with controls. No adverse outcomes including myocardial infarction, recurrent stroke, and mortality were observed in the both groups. Conclusion: Patients with ischemic stroke who received oral minocycline daily for 5 days had significantly better neurological outcomes on day 90 than controls. However, females showed no significant clinical improvement compared to males.